DEVELOPMENT OF ANDROID-BASED MATHEMATICS E-MODULE WITH SCIENTIFIC APPROACH TO ENHANCE PROBLEM-SOLVING SKILLS IN GRADE XI - Dessela, Syilvi; Asmar, Ali; Yerizon, Yerizon (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The research is designed to implement an Android mathematics e-module integrated with a scientific approach to uplift the students' skills in problem solving mathematically, especially in Grade XI. The basis of this research was for a more interactive and contextual learning media that could respond well to the novelty of digital native learners and the demands of 21st-century education. The Educational Design Research (EDR) method using the Plomp model was applied in this study. The study went through three major phases of the research process: preliminary research, prototyping, and assessment. The e-module was validated by experts as well as being practically and effectively tested through individual, small group, and large group evaluations and teacher responses. The findings showed that the e-module met validity criteria in terms of content, language, and design. Practicality was indicated from students and educators-to use it conveniently, and interesting from visual display, effective in arranging the contents systematically. Effectiveness testing also showed significant improvement in students' capabilities in solving mathematics problems through posttest scores and N-Gain results. The scientific phases of observing, questioning, experimenting, reasoning, and communicating were implemented within the Android platform, successfully fostering critical thinking as well as independence and meaningful learning. In conclusion, the e-module developed is a pedagogically sound and technologically accessible learning medium, geared towards developing higher-order thinking skills in mathematics, thus providing a valid alternative to classroom instruction.